2008
DOI: 10.4049/jimmunol.180.1.590
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αDβ2 Is Dynamically Expressed by Inflamed Macrophages and Alters the Natural History of Lethal Systemic Infections

Abstract: The leukocyte integrins have critical roles in host defense and inflammatory tissue injury. We found that integrin αDβ2, a novel but largely uncharacterized member of this family, is restricted to subsets of macrophages and a small population of circulating leukocytes in wild-type mice in the absence of inflammatory challenge and is expressed in regulated fashion during cytokine-induced macrophage differentiation in vitro. αDβ2 is highly displayed on splenic red pulp macrophages and mediates their adhesion to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(72 citation statements)
references
References 63 publications
(147 reference statements)
3
68
1
Order By: Relevance
“…Integrin α D β 2 mediates adhesion of murine and human leukocytes and cell lines in vitro [14],[24],[25],[30], consistent with adhesive activities of β 2 integrins that contribute to leukocyte targeting and localization [1][5],[8]. Integrins, including leukocyte integrins, also transmit “outside-in” signals that are linked to key intracellular transduction cascades [1],[4],[48],[49].…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Integrin α D β 2 mediates adhesion of murine and human leukocytes and cell lines in vitro [14],[24],[25],[30], consistent with adhesive activities of β 2 integrins that contribute to leukocyte targeting and localization [1][5],[8]. Integrins, including leukocyte integrins, also transmit “outside-in” signals that are linked to key intracellular transduction cascades [1],[4],[48],[49].…”
Section: Resultsmentioning
confidence: 59%
“…Indirect experiments by other investigators suggest that α D β 2 also potentiates the release of interferon gamma by human natural killer cells [21],[22]. Consistent with these observations, targeted deletion of α D in mice – resulting in absence of α D β 2 – yielded changes in cytokine and chemokine profiles in experimental models of malaria and Salmonella infection ([14]; manuscript submitted). The latter experiments suggest that outside-in signaling resulting from engagement of α D β 2 regulates inflammatory chemokine and cytokine synthesis in vivo , as well as in vitro .…”
Section: Discussionmentioning
confidence: 64%
“…It has been shown that anti-CD11d antibody reduced the inflammation (57) and macrophage accumulation (42,43) after spinal cord injury and CD11d-deficiency has a protective effect during P. berghei malaria infection (9). In contrast, the survival of CD11d −/− mice after Salmonella typhimurium sepsis was reduced (8). Despite different outcomes, these results demonstrate that CD11d alters the systemic inflammatory response during acute inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in comparison to other β 2 integrins, there is limited information on the function of CD11d/CD18. There are only a few publications that demonstrate the effect of CD11d on the development of the inflammatory response, and these have been studied in models of spinal cord injury (57), lethal systemic infections (8) and malaria (9). However, the molecular mechanism of CD11d function is still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…This feature appears to be a shared trait among KLFs because a similar regulatory loop was described for KLF4 (GKLF) (69). KLF4 also has been implicated in the regulation of integrins, because among myeloid cells KLF4 represses CD11d expression (70), an integrin (a D ) specifically expressed by red pulp macrophages (71). Thus, many evidences point to a general involvement of KLFs in the positioning of lymphocytes, particularly by regulating integrin expression.…”
Section: Gfpmentioning
confidence: 99%